Human Wharton's jelly mesenchymal stem cells show unique gene expression compared with bone marrow mesenchymal stem cells using single-cell RNA-sequencing - Barrett, Angela N. (2021)
Human Wharton's jelly stem cells (hWJSCs) isolated from the human umbilical cord are a unique population of mesenchymal stem cells (MSCs) with significant clinical utility. Their broad differentiation potential, high rate of proliferation, ready availability from discarded cords, and prolonged maintenance of stemness properties in culture make them an attractive alternative source of MSCs with therapeutic value compared with human bone marrow MSCs (hBMMSCs). We aimed to characterize the differences in gene expression profiles between these two stem cell types using single-cell RNA sequencing (scRNA-Seq) to determine which pathways are involved in conferring hWJSCs with their unique properties. We identified 436 significantly differentially expressed genes between the two cell types, playing roles in processes, including immunomodulation, angiogenesis, wound healing, apoptosis, antitumor activity, and chemotaxis. Expression of immune molecules is particularly high in hWJSCs compared with hBMMSCs. These differences in gene expression may help to explain many of the advantages that hWJSCs have over hBMMSCs for clinical application. Although cell surface protein marker expression indicates that isolated hWJSCs and hBMMSCs are both homogenous populations, using scRNA-Seq we can clearly identify extreme variability in expression levels between individual cells within a certain cell type. If the cells are examined as bulk populations, it is not possible to appreciate that a single cell may be making a major unique contribution to the apparent overall expression level. We demonstrated how the fine tuning of expression within hWJSCs and hBMMSCs may be achieved by expression of molecules with opposing function between two cells. We hypothesize that a greater understanding of these differences in gene expression between the two cell types may aid in the development of new therapies using hWJSCs.